Naked spirituality : a life with God in 12 simple words - McLaren, Brian D., 1956- (New York, NY : HarperOne, 2011)
"Many people are stuck with an understanding of prayer that doesn't go beyond Sunday school memorizations and desperate petitions in time of need. Instead, Brian McLaren argues we should understand that prayer is to the soul what breathing is to the body; prayer is life-giving union with the Divine. McLaren offers new hope to those who are disillusioned by religious dogma and disheartened by unanswered prayers. This is a book for those who want to pray but don't know where to start, a how-to book on the spiritual practice of prayer. In Naked Spirituality, McLaren confronts how the church's traditional practices no longer work; in fact, they often serve to prevent the very transformation God is calling us to undergo. As a result, religion becomes a tool to maintain the status quo and not an instrument for getting us closer to living as citizens of heaven. McLaren offers twelve moves, or practices, that both connect us with God and free us to do the holistic work the gospel calls us to--to pray as well as save the planet; to worship as well as lift up the poor and needy. For many people, McLaren's agenda for spirituality will feel like a formula for the faith they always hoped for and what they always knew Christianity should be about. With his characteristic fresh voice and practical wisdom, McLaren has written a spiritual manual that goes beyond encouraging piety by offering spiritual transformation"--
Spiritual experiences and spiritual experience ; "But I'm spiritual" ; Twelve simple words -- Simplicity : the season of spiritual awakening. Here : starting right now ; Here : naming the mystery ; Thanks : the happiness of appreciation ; Thanks : Dayenu : enough and more, and more ; O : practicing jubilation ; O : not just a word, a way of life -- Complexity : the season of spiritual strengthening. Sorry : holier than myself? ; Sorry : unleashing our own becoming ; Help : spiritual jujitsu ; Help : tapping into the current of power ; Please : at least two hearts care ; Please : bearing the stretcher-- Perplexity : the season of spiritual surviving. When : how long can I last? ; When : survival is underrated ; No : the void expands ; No : mad with God ; Why : when you have come to zero ; Why : holding the question open -- Harmony : the season of spiritual deepening. Behold : the emergence of the meditative mind ; Behold : faith beyond belief ; Yes : a universal spiritual vocation ; Yes : do you love me? ; [ ... ] : naked, clothed in silence ; [ ... ] : full circle -- The sea toward which all rivers run -- Appendix A. Group practice - -Appendix B. Body prayers -- Appendix C. Twelve simple prayers.
Includes bibliographical references.
Keywords: Spiritual life -- Christianity; Prayer -- Christianity; Christian life; RELIGION / General